Generation of Chemisorbed Benzyl Radicals on Silica Nanoparticles - Arce, Valeria Beatriz (2010)
Functionalized silica nanoparticles (NP) were obtained by esterification of the silanol groups of fumed silica nanoparticles with benzyl alcohol. These particles were characterized by Fourier transform infrared spectroscopy, 13C and 29Si NMR spectroscopy, thermogravimetry, total organic carbon, Brunauer– Emmett–Teller analysis, UV-visible spectroscopy, and transmission electron microscopy. NP suspensions in water ⁄ acetonitrile mixtures were used as quenchers of benzophenone (BP) phosphorescence in time-resolved experiments at the excitation wavelength of 266 nm. The phosphorescence signals obtained in the presence of the nanoparticles were fitted to biexponential decays. Both decays were accelerated in the presence of increasing amounts of NP. A model, including the reversible adsorption of BP on the NP, which was supported by computer simulations accounts for the observed results. Laser flash-photolysis experiments with excitation at 266 nm of NP suspensions in water/acetonitrile in the presence of BP generated benzyl radicals that were attached to the silica surface. These radicals were detected at their absorption maxima (320 nm) by transient optical techniques.13C and 29Si NMR spectroscopy, thermogravimetry, total organic carbon, Brunauer– Emmett–Teller analysis, UV-visible spectroscopy, and transmission electron microscopy. NP suspensions in water ⁄ acetonitrile mixtures were used as quenchers of benzophenone (BP) phosphorescence in time-resolved experiments at the excitation wavelength of 266 nm. The phosphorescence signals obtained in the presence of the nanoparticles were fitted to biexponential decays. Both decays were accelerated in the presence of increasing amounts of NP. A model, including the reversible adsorption of BP on the NP, which was supported by computer simulations accounts for the observed results. Laser flash-photolysis experiments with excitation at 266 nm of NP suspensions in water/acetonitrile in the presence of BP generated benzyl radicals that were attached to the silica surface. These radicals were detected at their absorption maxima (320 nm) by transient optical techniques.⁄ acetonitrile mixtures were used as quenchers of benzophenone (BP) phosphorescence in time-resolved experiments at the excitation wavelength of 266 nm. The phosphorescence signals obtained in the presence of the nanoparticles were fitted to biexponential decays. Both decays were accelerated in the presence of increasing amounts of NP. A model, including the reversible adsorption of BP on the NP, which was supported by computer simulations accounts for the observed results. Laser flash-photolysis experiments with excitation at 266 nm of NP suspensions in water/acetonitrile in the presence of BP generated benzyl radicals that were attached to the silica surface. These radicals were detected at their absorption maxima (320 nm) by transient optical techniques.